Práticas de letramento e ensino remoto nos anos iniciais: um estudo complexo e transdisciplinar - Satyro, Diego (2023)
This research investigates the phenomenon literacy practices, mediated by digital technologies, in the early years of elementary school, experienced during the pandemic period, in a public school in São Bernardo do Campo (SP). The literature review draws on Complex Thinking (MORIN, 2000, 2003, 2005, 2015), Transdisciplinarity (NICOLESCU, 2000, 2015, 2020) and Literacy Studies (STREET, 2014; KLEIMAN, 2008; BARTON & HAMILTON, 2012; SIGNORINI, 2007, 2012, 2013; KALANTZIS, COPE & PINHEIRO, 2020; ROJO, 2013, 2017; ROJO & MOURA, 2019). The methodological orientation is the complex hermeneutic-phenomenological approach (FREIRE, M., 2010, 2012, 2017), which aims at the description and interpretation of complex phenomena of human experience. Thirteen teachers and fourteen students (third and fifth graders) of a municipal school participated in the study, followed in their remote activities during the period of four months. The interpretation of the phenomenon, according to the procedures of the adopted approach, revealed ten complex hermeneutic-phenomenological themes: digital technologies, family, subversion, mimicry, innovation, facilitation, evaluation, interaction, learning and time. Considering the contents of these themes, it is possible to interpret that literate practices in remote teaching occur in an intermittent flow between practices of the graph-centric tradition and hypermedia practices, in addition to an impulse to more innovative practices though the use of technologies, despite the overwhelming experience for the teachers involved. The relevance of the research lies not only in its documental nature of the pandemic period, but above all in its pedagogical character, by reflecting on the potentialities and restrictions posed by remote teaching. The study also contributes to a re-signification of literacy studies in interface with schooling, in a complex and transdisciplinary perspective, in dialogue with the sociocultural approach (CARVALHO, 2003)